HAMBATAN KOMUNIKASI DALAM PEMBELAJARAN EKONOMI DI KELAS XI IIS SMA NEGERI 1 AIR BESAR KABUPATEN LANDAK - Grasela, Yovita Mega; Ulfah, Maria; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The aim of this research is to find out the factors that hinder communication in economics learning and find out how to overcome the factors that hinder communication in economics learning. The method of this research is descriptive qualitative which directly explains the circumstances that occurred in this research. This research used 10 sources, 1 economic subject teacher as the key informant, 6 students as the main informant, the school principal as additional informant, the deputy principal for curriculum as additional informant and administration as additional informant. data collection techniques using interviews, observation and documentation. Data analysis uses 3 stages, namely data reduction, data presentation and drawing conclusions and verification. Data validity checking techniques use source triangulation and technical triangulation. research results (1) factors inhibiting communication in economics learning in class (2) how to overcome factors inhibiting communication in economics learning in class systematic so that it is easy to understand, giving space for students to ask questions, using language that is easy to understand and avoiding the use of difficult vocabulary, encouraging students to ignore their own opinions and accept the opinions of others who differ from their opinions.